HAK ASASI DAN KEWAJIBAN MORAL MANUSIA DALAM PERSPEKTIF RICHARD RORTY - john abraham ziswan (Arete, 2019)
Tounderstandhumanrightsandmoralobligationsisoftenassociatedwithanorm system that rigid and binding. But the evolution of technology cannot closeour eyes that there is a movement of changes that are continuallyoccurring andproducing some variety of possibilities. In this condition, the writer wants to try toexplain the concept of human rights and moral obligations by using the approachof neo-pragmatism from Richard Rorty. In this case, Richard Rorty consideredhumanrightsandmoralobligationsasacontingency,thathedidnottrytorefertorepresentative truth, but he based himself on an openness. The eJort of the writeris in order to get the correlation of the development of human life nowadays withRichardRorty’sneo-pragmaticparadigm.